Best Served Cold: Vengeful Attitudes and Violence among Finnish Adolescents. Issue 2 (1st February 2022) - Lowe, C. Cory; Ellonen, Noora; Lee Miller, Bryan; Peltonen, Kirsi
ABSTRACT: Research has identified several predictors of violence; however, few studies have examined the role of revenge as a motivating factor of violent delinquency. In this study, we use multilevel logistic regression models to examine the relationship between beliefs favorable to revenge and violent behavior among a random sample of 6061 adolescents in Finnish schools. The results show that established predictors of violence, such as peer delinquency, unstructured socializing, and violent victimization are all significantly associated with violent behavior. However, attitudes supporting revenge also emerge as a significant predictor of violence even after controlling for other factors. This finding reinforces research suggesting that violence-reduction interventions and initiatives should attempt to promote prosocial means of conflict resolution and reduce beliefs favorable to violence such as support for revenge.